Reduction of myocardial ischaemia–reperfusion injury by inactivating oxidized phospholipids. Issue 1 (30th May 2018) - Yeang, Calvin; Hasanally, Devin; Que, Xuchu; Hung, Ming-Yow; Stamenkovic, Aleksandra; Chan, David; Chaudhary, Rakesh; Margulets, Victoria; Edel, Andrea L; Hoshijima, Masahiko; Gu, Yusu; Bradford, William; et al.
Abstract: Aims: Myocardial ischaemia followed by reperfusion (IR) causes an oxidative burst resulting in cellular dysfunction. Little is known about the impact of oxidative stress on cardiomyocyte lipids and their role in cardiac cell death. Our goal was to identify oxidized phosphatidylcholine-containing phospholipids (OxPL) generated during IR, and to determine their impact on cell viability and myocardial infarct size. Methods and results: OxPL were quantitated in isolated rat cardiomyocytes using mass spectrophotometry following 24 h of IR. Cardiomyocyte cell death was quantitated following exogenously added OxPL and in the absence or presence of E06, a 'natural' murine monoclonal antibody that binds to the PC headgroup of OxPL. The impact of OxPL on mitochondria in cardiomyocytes was also determined using cell fractionation and Bnip expression. Transgenic Ldlr −/− mice, overexpressing a single-chain variable fragment of E06 ( Ldlr −/− -E06-scFv-Tg) were used to assess the effect of inactivating endogenously generated OxPL in vivo on myocardial infarct size. Following IR in vitro, isolated rat cardiomyocytes showed a significant increase in the specific OxPLs PONPC, POVPC, PAzPC, and PGPC ( P  < 0.05 to P  < 0.001 for all). Exogenously added OxPLs resulted in significant death of rat cardiomyocytes, an effect inhibited by E06 (percent cell death with added POVPC was 22.6 ± 4.14% and with PONPC was 25.3 ± 3.4% compared to 8.0 ± 1.6% and 6.4 ± 1.0%, respectively, with the addition of E06, P  < 0.05 for both). IR increased mitochondrial content of OxPL in rat cardiomyocytes and also increased expression of Bcl-2 death protein 3 (Bnip3), which was inhibited in presence of E06. Notably cardiomyocytes with Bnip3 knock-down were protected against cytotoxic effects of OxPL. In mice exposed to myocardial IR in vivo, compared to Ldlr −/− mice, Ldlr −/− -E06-scFv-Tg mice had significantly smaller myocardial infarct size normalized to area at risk (72.4 ± 21.9% vs. 47.7 ± 17.6%, P  = 0.023). Conclusions: OxPL are generated within cardiomyocytes during IR and have detrimental effects on cardiomyocyte viability. Inactivation of OxPL in vivo results in a reduction of infarct size.